1998
DOI: 10.1001/archneur.55.7.915
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic Inclusion-Body Myositis and Hereditary Inclusion-Body Myopathies

Abstract: S poradic inclusion-body myositis and hereditary inclusion-body myopathies are progressive and highly debilitating muscle diseases. The most characteristic morphologic feature of sporadic inclusion-body myositis and hereditary inclusion-body myopathies is vacuolar degeneration of muscle fibers, accompanied by intrafiber clusters ("tangles") of paired-helical filaments and by accumulation of several proteins that are characteristic of a brain of patients with Alzheimer disease. In neither the hereditary inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 19 publications
(19 reference statements)
0
33
0
Order By: Relevance
“…Mitochondrial dysfunction and oxidative stress, which is increased in s-IBM muscle fibres [23][24][25] , are known to stimulate aggregation of amyloidogenic proteins 26 . Moreover, overexpression of βAPP and accumulation of amyloid-β are early changes in muscle fibres prior to the development of structural abnormalities 27 , and over-expression of βAPP in human myoblasts in vitro leads to the development of structural mitochondrial abnormalities and loss of COX activity 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction and oxidative stress, which is increased in s-IBM muscle fibres [23][24][25] , are known to stimulate aggregation of amyloidogenic proteins 26 . Moreover, overexpression of βAPP and accumulation of amyloid-β are early changes in muscle fibres prior to the development of structural abnormalities 27 , and over-expression of βAPP in human myoblasts in vitro leads to the development of structural mitochondrial abnormalities and loss of COX activity 28 .…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal deposition of cross-linked proteins including amyloids and other unknown proteins may induce muscle fiber destruction in s-IBM, as proposed by Askanas and Engel [4]. Interestingly, we found that the total TGase activity was elevated 16-fold in the diseased tissue, which is reflected in an increased number of products from TGase catalysis, ε(γ-glutamyl)lysine cross-links, from ∼2/10,000 in normal muscle to ∼60/10,000 residues [18].…”
Section: Discussionmentioning
confidence: 99%
“…They are sharing the common and characteristic feature of muscle degeneration mediated by an inflammatory process [1, 2, 3, 4]. IMs are currently treated with immunosuppressants or immunomodulating drugs.…”
Section: Introductionmentioning
confidence: 99%
“…1 The abbreviations used are: AD, Alzheimer's disease; HSV, herpes simplex virus; A␤ (42), ␤-amyloid peptide ( necrotic, atrophic, angulated myofibers (18). Their sparse occurrence, however, make it likely that clinical muscle weakness arises from a more widespread or generalized metabolic defect, for instance related to oxidative stress (19) that can possibly lead to mitochondrial failure, calcium dyshomeostasis and/or a disorder of filament function and cytoskeletal protein interactions. Calcium dysregulation for example, could be limited to myofibers affected with inclusions or also involve normal appearing myofibers, which harbor undetectable but nevertheless toxic levels of intracellular soluble oligomeric ␤-amyloid species (see Ref.…”
mentioning
confidence: 99%